Application Status and Analysis of Starlink Constellation - Yu WANG; Qing LI; Kejun LI; Changlin JIANG; Ye WANG; Yong JIANG; Mingwei XU (天地一体化信息网络)
Starlink, asatellite broadband constellation operated by SpaceX, is currently the most influential and promising LEO broadband satellite constellation.With the expansion of the constellation deployment, its high-frequency launch and batch deployment of satellites, provision of diversified satellite broadband services, rapid growth of global user terminals, as well as potential support and capability enhancing for military are manifesting gradually.Firstiy, the current status of Starlink's on-orbit operations were analyzed, and its internet services with other satellite broadband service providers was compared.Then, the application characteristics and technical challenges of Starlink's inter-satellite laser links were focused on, and Starlink's military application progress and the evolution trend were discussed.Finally, the comprehensive application advantages Starlink offers, and technical challenges faced by Starlink were summarized, which could served as a stepping stone for the design of our country's satellite network.Overall, the construction and application of a mega LEO constellation like Starlink involves the chain integration of a series of component, ranging from satellite design and industrialized production, satellite launch facilities, constellation operation and maintenance, satellite networking, toglobal ground station supporting, rather than just the satellite platforms.